ANALYSIS OF FINANCIAL ACCOUNTABILITY IN THE FINANCE WORK UNIT (SATKER) OF POLRI HEADQUARTERS (Case Study at the Financial Center / PUSKEU Police Headquarters in accordance with PERKAP No. 22 of 2011) - Sekar Nurtilawah; Arni Karina; Kumba Digdowiseiso (SEAN Institute, 2023)
The Financial Sector Work Unit is one of the accounting entities under the Police Agency which is obliged to carry out accounting and accountability reports in order to realize the effective, efficient, transparent and accountable implementation of the duties of the National Police of the Republic of Indonesia. The aim of the research is to find out whether the implementation of the financial management of the National Police Public Health Unit's financial management unit is running well in accordance with Perkap No. 22 of 2011 in Chapter II Article 4. The contribution of this research is to provide knowledge regarding financial accountability in the work unit (SATKER) in the financial sector of POLRI Headquarters regarding PERKAP No. 22 of 2011. It is hoped that it can enrich academic documents which are useful as complementary information for further research. The research method used is qualitative descriptive research. The results of the research concluded that financial accountability had been carried out well or in accordance and the Accounting Policy implemented was in accordance with Minister of Finance Regulation Number 225 /PMK.05/2016 and the Polri Public Health Center Accountability Report was in accordance with PERKAP No. 22 of 2011.